AMPLITUDE, TRAJECTORY AND AFFERENT PARAMETERS ANALYSIS OF THE JUMP OVER A VERTICAL FENCE IN SPORT HORSES - FLAVIA BOCHIS; GABI DUMITRESCU; ELIZA SIMIZ; I. TRIPON; F. SIMIZ (Scientific Papers Animal Science and Biotechnologies, 2023)
There are a lot of obstacles type used in jumping competitions. Normally, for every kind of fence, there is a different type of approaching and cross over. The most used obstacles are the vertical fence and the oxer fence. For crossing over the vertical, which is a high fence, the horse must jump only in report to the height of the bar. In the oxer case, which is a large obstacle, the horse must jump related to the height and the largeness of it indeed. In the present study we obtained for the vertical fence, situated at five different levels. The purpose was to measure four parameters for every jump: the taking-off distance, the landing distance, and the distance between bar and legs for the front limbs and for the hind limbs. Based on these, were calculated in report to the type of the show arena the amplitude of the jumps, was assign the trajectory curve and placed the balance point.